RESPON BERBAGAI KONSENTRASI DAN INTERVAL PUPUK DAUN GROWMORE TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KANGKUNG DARAT (Ipomea reptans Poir) - Fiona Grace Yulia; Elza Zuhry (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
The purpose of this study was to increase the growth and production of land kangkung plants that were given Growmore leaf fertilizer at different intervals, and to obtain the best concentration and interval of fertilizer application. The research was carried out in the yard of the house, Pondok II Libo RW 10 RT 001, Libo Jaya Village, Kandis District, Siak. The study lasted for one month from August to September 2021. The study was carried out experimentally using a completely randomized design (CRD), consisting of 2 treatments and 3 replications with Growmore fertilizer concentration and spraying intervals. Parameters observed were plant height, stem diameter, number of leaves, canopy wet weight, root wet weight, leaf fresh weight, shoot dry weight, root dry weight, and total chlorophyll content. The data obtained were analyzed statistically using variance. The results of the variance were continued with Duncan's multiple distance test at the 5% level. The results showed that the application of Growmore fertilizer at various concentrations and intervals of spraying could increase plant height, number of leaves, wet weight of roots, fresh weight of leaves, and total chlorophyll content. The application of Growmore fertilizer with 3 g.l-1 of water at intervals of3 days increased the growth of the kale. The application of Growmore fertilizer with different concentrations did not increase the growth and production of kale, meanwhile the interval of spraying Growmore fertilizer once every 3 days can increase the wet weight of the roots and the wet weight of the crown. Keywords: Growmore foliar fertilizer, land kale, concentration, spraying interval